To write the equation 0.4x + 0.2y = 0.6 in slope-intercept form, we need to isolate y on one side of the equation.
0.2y = -0.4x + 0.6
y = -2x + 3
Therefore, the equation 0.4x + 0.2y = 0.6 in slope-intercept form is y = -2x + 3.
write 0.4x + 0.2y = 0.6 in slope-intercept form.
11 answers
write the linear equation 3y=6x-18 in slope-intercept form.
To write the equation 3y = 6x - 18 in slope-intercept form, we need to isolate y on one side of the equation.
Divide both sides of the equation by 3:
y = 2x - 6
Therefore, the equation 3y = 6x - 18 in slope-intercept form is y = 2x - 6.
Divide both sides of the equation by 3:
y = 2x - 6
Therefore, the equation 3y = 6x - 18 in slope-intercept form is y = 2x - 6.
what is the slope and y-intercept of the equation 9 + 27/2x = -3/2y? write the y-intercept as an ordered pair.
To find the slope-intercept form of the given equation, we need to solve for y.
9 + (27/2)x = (-3/2)y
Divide both sides by (-3/2):
y = -3/2(9 + 27/2x)
y = -13.5 - 20.25x
y = -20.25x - 13.5
Therefore, the slope of the equation is -20.25 and the y-intercept is -13.5, which can be written as the ordered pair (0, -13.5).
9 + (27/2)x = (-3/2)y
Divide both sides by (-3/2):
y = -3/2(9 + 27/2x)
y = -13.5 - 20.25x
y = -20.25x - 13.5
Therefore, the slope of the equation is -20.25 and the y-intercept is -13.5, which can be written as the ordered pair (0, -13.5).
wrong
Let's correct that:
To find the slope-intercept form of the given equation:
9 + \(\frac{27}{2}x = \frac{-3}{2}y\)
First, let's simplify the equation by multiplying through by -2 to eliminate the fraction:
-18 - 27x = 3y
Now divide through by 3 to isolate y:
y = -9 - 9x
Comparing this with the slope-intercept form, y = mx + b, we can see that the slope is -9, and the y-intercept is -9, which can be written as the ordered pair (0, -9).
To find the slope-intercept form of the given equation:
9 + \(\frac{27}{2}x = \frac{-3}{2}y\)
First, let's simplify the equation by multiplying through by -2 to eliminate the fraction:
-18 - 27x = 3y
Now divide through by 3 to isolate y:
y = -9 - 9x
Comparing this with the slope-intercept form, y = mx + b, we can see that the slope is -9, and the y-intercept is -9, which can be written as the ordered pair (0, -9).
y-intercept is wrong.
I apologize for the mistake. Let's correct the y-intercept:
To find the y-intercept, we can plug in x = 0 into the equation y = -9 - 9x:
y = -9 - 9(0)
y = -9
Therefore, the correct y-intercept is -9, which can be written as the ordered pair (0, -9).
To find the y-intercept, we can plug in x = 0 into the equation y = -9 - 9x:
y = -9 - 9(0)
y = -9
Therefore, the correct y-intercept is -9, which can be written as the ordered pair (0, -9).
still wrong!!!
My apologies for the oversight. Let's correct it:
Given equation: 9 + \(\frac{27}{2}\)x = \(\frac{-3}{2}\)y
To find the slope-intercept form, we'll first solve for y:
\(\frac{27}{2}\)x = \(\frac{-3}{2}\)y - 9
Multiplying by 2/3 to isolate y, we get:
y = -9(2/3) - (27/2)(2/3)x
y = -6 - 9x
The equation is now in slope-intercept form, y = -9x - 6.
The slope of the equation is -9, and the y-intercept is -6, which can be written as the ordered pair (0, -6).
Given equation: 9 + \(\frac{27}{2}\)x = \(\frac{-3}{2}\)y
To find the slope-intercept form, we'll first solve for y:
\(\frac{27}{2}\)x = \(\frac{-3}{2}\)y - 9
Multiplying by 2/3 to isolate y, we get:
y = -9(2/3) - (27/2)(2/3)x
y = -6 - 9x
The equation is now in slope-intercept form, y = -9x - 6.
The slope of the equation is -9, and the y-intercept is -6, which can be written as the ordered pair (0, -6).